Management information systems of laboratory using laravel framework:case study at electrical engineering of Universitas Negeri Semarang - Muhammad Irfan Hammam Zuhdi; Subiyanto Subiyanto; Sri Sukamta (Jurnal Pendidikan Vokasi, 2017)
The distribution of services using information system technology greatly helps stakeholders. There were still frequent errors found in the management of scheduling lab work in the Laboratory services which had not using the laboratory information system yet. This paper presents the development of laboratory management information system which facilitate scheduling lab work, a case study at Electrical Engineering Laboratory of UniversitasNegeri Semarang. The steps of constructing this system started from the data collection phase, design phase, and construction phase. This information system was built by using laravel framework based on MVC (Model-View- Controller). The system was created by using PHP programming language and MySQL database. The information system was created to ease and facilitate the Chairman of the Laboratory, Laboratory Institution of Education, and students in monitoring laboratory activities, including data lab work, voting laboratory scheduling data, the data of lecturers, the data of subjects and laboratory data of Electrical Engineering . Based on the test result, SIMLAB is effective enough to be applied in Electrical Engineering laboratory Universitas Negeri Semarang.